SAT-634 The Effect of Continine Verified Smoking on the Development of Diabetes - Jung, Inha (J Endocr Soc, 2020)
Background: Cigarette smoking is a major public health problem and the leading cause of death. We aimed to analyze the effects of cotinine verified smoking on the development of diabetes mellitus. Methods: Among individuals enrolled in the Kangbuk Samsung Health Study and Kangbuk Samsung Cohort Study, a total of 17,626 men (mean age 37.9 years) who underwent a health screening program in 2011 and 2017 were enrolled. Anthropometric and biochemical parameters, including urinary cotinine level were measured. The odds ratios (OR) for the presence of diabetes were analyzed in three groups according to their self-reported smoking status (Never smoker; Quitter and Current smoker) and cumulative amount of smoking. Individuals with urinary cotinine levels>50 ng/mL were defined as cotinine-verified current smokers. Results: Among the total participants without diabetes at baseline, 605 (3.4%) participants had diabetes after 6 years. The risk for diabetes was lower in nonsmokers than in current smokers and quittters after adjusting for confounding factors (OR 0.71; 95% confidence interval (CI)0.56-0.89) with current smokers as the reference group. The risks of diabetes were gradually increased with amount of smoking in both quitters and current smokers. When the participants were analyzed in subgroups according to the urinary cotinine levels, those with high urinary cotinine levels >500ng/mL showed the higher risk for the development of diabetes (OR 1.57; 95% CI 1.27 – 1.93). Conclusions: This study showed that cotinine-verified smoking was associated with the development of diabetes. Furthermore, there was a potential association between smoking amounts and the development of diabetes regardless of smoking cessation. We also found that those with high urinary cotinine levels showed an increased risk for diabetes compared with participants with low urinary cotinine levels.